Performance Management System Using Balanced Scorecard Framework and Analytical Hierarchy Process A Case Study In Indonesia Manufacturing Company - Hadiyanto, Haris; Wibisono, Dermawan (Syntax Literate, 2025)
Improving an increasingly competitive environment such as how easy it is for customers to get cheap and quality products from the import process pressures manufacturing companies to always increase their competitive advantage. It is important for a company to be able to anticipate threats and continuously update its strategy in order to maintain the performance of the company. This paper aims to identify, analyze, and define key performance indicators (KPI) for one of the manufacturing companies in Indonesia with the first step being to design the right performance management system (PMS) for the company. The integration of the Balanced Scorecard (BSC) and the Analytical Hierarchy Process (AHP) introduces a structured, data-driven approach to prioritizing key performance indicators (KPIs), enabling manufacturing companies like PT ABCD to align strategic objectives with operational performance more effectively, thereby enhancing decision-making accuracy and competitive advantage in a highly dynamic market. The balanced scorecard approach was used in this research to determine the right KPIs and were determined through focus group discussions with top management. The KPIs that have been set are then analyzed using the Analytical Hierarchy Process (AHP) to determine how the relationships between these KPIs are. The finding of this paper is to provide KPIs that companies can use as a first step in measuring the performance of manufacturing companies in Indonesia.